A glimpse on biological activities of tellurium compounds - Cunha,Rodrigo L. O. R. (2009)
Tellurium is a rare element which has been regarded as a toxic, non-essential trace element and its biological role is not clearly established to date. Besides of that, the biological effects of elemental tellurium and some of its inorganic and organic derivatives have been studied, leading to a set of interesting and promising applications. As an example, it can be highlighted the uses of alkali-metal tellurites and tellurates in microbiology, the antioxidant effects of organotellurides and diorganoditellurides and the immunomodulatory effects of the non-toxic inorganic tellurane, named AS-101, and the plethora of its uses. Inasmuch, the nascent applications of organic telluranes (organotelluranes) as protease inhibitors and its applications in disease models are the most recent contribution to the scenario of the biological effects and applications of tellurium and its compounds discussed in this manuscript.